2018
DOI: 10.3855/jidc.10560
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of extended-spectrum β-lactamase producing Escherichia coli from hospital settings in Yemen

Abstract: Introduction: Infection with Extended spectrum β-lactamases (ESBLs) producing bacteria is considered as serious health problem worldwide. The aim of this cross-sectional study was to investigate the prevalence of ESBL producing Escherichia coli in hospitalized patients and the risk factors contributed for its nosocomial infections in addition to the antibiotics susceptibility patterns of isolates from 130 inpatients collected in Al Thawra General Hospital and Al-Kuwait University Hospital in Sana’a city. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…These studies demonstrated slightly higher levels of resistance to various antimicrobials. For example, between 2014 and 2018, the resistance to cefuroxime was 95%, amoxycillin-clavulanate 90.9%, ciprofloxacin 90.9%, meropenem 95% and imipenem 95% [ 63 , 64 ]. The increase in antibiotic resistance in these isolates was also justified by the detection of β-lactamases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies demonstrated slightly higher levels of resistance to various antimicrobials. For example, between 2014 and 2018, the resistance to cefuroxime was 95%, amoxycillin-clavulanate 90.9%, ciprofloxacin 90.9%, meropenem 95% and imipenem 95% [ 63 , 64 ]. The increase in antibiotic resistance in these isolates was also justified by the detection of β-lactamases.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from Yemen revealed the phenotypic prevalence of ESBLs in E. coli and ESKAPE pathogens. These studies showed that during the study period the phenotypic prevalence of ESBL increased from 33% to 100% [ 63 , 64 ]. Furthermore, analysis based on PCR studies was also undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were conducted in Lebanon (Beirut and Byblos) [ 22 , 23 ], two in Iraq (Baghdad and Kurdistan) [ 24 , 25 ], one in Jordan (Ar Ramtha) [ 26 ], one in Palestine (Gaza) [ 27 ] and one in Yemen (Sana’a) [ 28 ]. The study population (total of 5833 participants) was composed of: 1- Syrian refugees with acute conflict injuries [ 26 ], 2- military and civilian populations with conflict-inflicted injuries [ 24 ], and 3- either civilians or undetermined populations in the five remaining studies.…”
Section: Resultsmentioning
confidence: 99%
“…The study population (total of 5833 participants) was composed of: 1- Syrian refugees with acute conflict injuries [ 26 ], 2- military and civilian populations with conflict-inflicted injuries [ 24 ], and 3- either civilians or undetermined populations in the five remaining studies. The results consisted of three retrospective chart reviews [ 23 – 25 ], one cross-sectional study [ 28 ], one case-control study [ 27 ], one nested case-control [ 22 ] and two prospective cohorts [ 22 , 26 ]. All studies were hospital-based but only three were multicenter, and half of the studies were conducted in intensive care units with or without including other hospital wards [ 22 , 24 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation